Luxação Bilateral Congênita de Joelho - um caso de redução espontânea - Mariana Penteado Borges; Larissa Vieira Del Core Barbosa; Julia Barcelos Braglia; Isadora da Silveira; Rosana Loureiro (Residência Pediátrica)
Congenital knee dislocation (CKD), or genu recurvatum, is a disorder that occurs in approximately 1 in every 100,000 live births, with nearly equal distribution between sexes, defined by hyperextension of the knees present at birth. Involvement can be unilateral, which is more frequent, or bilateral, which is rare and accounts for about one-third of cases. The etiology of CKD is still uncertain, but it is believed that there is an association between factors such as breech fetal presentation, oligohydramnios, neuromuscular imbalances, and genetic malformations. Treatment of CKD includes conservative management, physical therapy, and surgical intervention, depending on the degree of dislocation classification. This report presents a newborn with bilateral knee dislocation, of positional etiology, diagnosed in the delivery room and later confirmed by X-ray, with no other associated musculoskeletal or genetic abnormalities found. The patient received conservative treatment, achieving spontaneous and complete resolution of the condition.